Strengthening Domestic Competitiveness through Halal Industry Governance and Islamic Management Practices - Desy Arum Sunarta; Riski Apriliani; Antonio Galli (PT. Islamic Research Publisher, 2024)
This study examines the role of halal industry governance and Islamic management practices in enhancing domestic competitiveness within the halal economy. It aims to synthesize and conceptualize existing scholarly evidence on how governance frameworks rooted in Islamic values contribute to strengthening the competitiveness of halal-based economic activities. Using a qualitative literature review approach, the study systematically analyzes peer-reviewed articles from reputable academic databases to identify dominant themes, theoretical orientations, and recurring empirical patterns. The findings indicate that effective halal industry governance, when supported by core Islamic management principles such as transparency, accountability, trustworthiness, and justice, plays a crucial role in strengthening institutional coordination, improving value chain efficiency, and enhancing market confidence. These interconnected factors collectively contribute to the reinforcement of domestic competitiveness in halal industries, particularly in emerging Muslim-majority economies where institutional maturity is still developing. The study concludes that the integration of Islamic management principles into halal governance frameworks not only ensures Sharia compliance but also generates measurable strategic and economic value. Academically, this research contributes to the literature by developing a synthesized conceptual framework that links halal governance, Islamic management principles, and domestic competitiveness within a single analytical structure. It extends existing discussions on halal industry development by moving beyond compliance-oriented perspectives toward a competitiveness-based paradigm. Furthermore, it enriches the fields of Islamic economics and management studies by demonstrating how value-based governance systems can function as drivers of institutional efficiency and market performance in emerging economies.